SILENCED IN CYBERSPACE: MUTED GROUP THEORY AND THE LIVED EXPERIENCES OF REVENGE PORN SURVIVORS IN BANJARMASIN - Noorjannah Noorjannah; Muhammad Alif (Kafa`ah: Journal of Gender Studies, 2026)
This study aims to analyze the patterns of silencing and the impacts of revenge porn, as well as why victims of revenge porn choose to remain silent. This research employs a qualitative approach with a phenomenological design, conducted in Banjarmasin City. Data collection techniques included interviews, observation, and documentation. Data analysis followed Moustakas' phenomenological analysis technique, consisting of epoche, phenomenological reduction, imaginative variation, and synthesis of meanings. The subjects of this study comprised five individuals selected through purposive sampling based on several criteria: female, aged 18–25 years, having experienced revenge porn, and residing in Banjarmasin City. The findings reveal that the silencing experiences of revenge porn victims involve threats, blackmail, and the dissemination of pornographic content. Additionally, the impacts felt by victims include trauma and depression. The reasons victims choose to remain silent are fear of disclosing their experiences and low self-esteem. Social support for victims emerges as a crucial factor in helping them recover from distress.